1993
DOI: 10.3109/01485019308988379
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Antiestrogens in Infertile Men

Abstract: Eighty-nine oligozoospermic men, treated by clomiphene or tamoxifen or with no treatment at all, were evaluated during a 4-year follow-up period. Ejaculate volume, sperm concentration, and sperm motility were determined and concentrations of prolactin (PRL), estradiol, beta hCG, prostaglandin E2, zinc, and fructose were ascertained. Isoenzyme LDH-C4 activity and serum PRL and follicle stimulating hormone were also determined. During treatment there was only a minimum increase in sperm concentration. No improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…On the other hand, several works demonstrated no significant efficacy of tamoxifen for the treatment of male infertility/idiopathic oligospermia (27,(41)(42)(43). Moreover, Rolf et al reviewed the treatment of male infertility in 29 clinical trials with a total of 1,586 patients and concluded that the benefits may not justify the risks (thrombocytopenia, carcinogenicity) of using tamoxifen in otherwise healthy males (44).…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, several works demonstrated no significant efficacy of tamoxifen for the treatment of male infertility/idiopathic oligospermia (27,(41)(42)(43). Moreover, Rolf et al reviewed the treatment of male infertility in 29 clinical trials with a total of 1,586 patients and concluded that the benefits may not justify the risks (thrombocytopenia, carcinogenicity) of using tamoxifen in otherwise healthy males (44).…”
Section: Discussionmentioning
confidence: 94%
“…In hypogonadal men with low-volume ejaculate, treatment with clomiphene citrate may increase testosterone levels, but its effects on ejaculate volume are unknown, although one report found no difference in ejaculate volume before and after treatment. 49 …”
Section: Treatmentmentioning
confidence: 99%
“…Dosages of 10-25 mg/kg were administered ranging over periods of 10 days to 9 months. Sperm motility, concentration, and morphology improved significantly in oligozoospermic patients (Micic and Dotlic, 1985;Hayashi et al, 1988;Homonnai et al, 1988;Breznik and Borko, 1993) (Table 9). More than 50% pregnancy rates were obtained in oligozoospermic patients and patients recovered from varicocelectomy not responding to hCG (Epstein, 1977).…”
Section: Hormonal Treatments Aimed At Natural Pregnanciesmentioning
confidence: 99%
“…Sperm motility was analyzed in 5 studies, of which none reported improvement (Maier and Hienert, 1990; Sterzik et al, 1991, 1993; Krause et al, 1992; Breznik and Borko, 1993). Among all 6 studies following up for pregnancy rates (Bartsch and Scheiber, 1981; Traub and Thompson, 1981; Buvat et al, 1983; Török, 1985; AinMelk et al, 1987; Breznik and Borko, 1993), values ranging from 12% to 40% pregnancy rates were reported. However, another study involving 89 subjects has reported higher pregnancy rates in the control group, along with an interesting observation of increase in seminal zinc and decrease in serum prolactin (PRL) levels (Breznik and Borko, 1993).…”
Section: Hormonal Treatments Aimed At Natural Pregnanciesmentioning
confidence: 99%
See 1 more Smart Citation